Course of pancreatic necrosis on a background of major duodenal papilla stone - S. V. Mikhaylusov; Ye. V. Moiseyenkova; M. M. Misrokov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate course of biliary pancreatic necrosis (PN) on a background of an «impacted» stone of major duodenal papilla in comparison to pancreatic necrosis of alimentary origin.Material and methods. Treatment results of 76 patients with PN (33 patients with a stone of major duodenal papilla — main group, 43 — alimentary PN — control group) were analyzed. Study inclusion criterion: availability of papilla to endoscopic inspection. In main group women prevailed, patients over 60 years of age. In patients with alimentary PN late hospital admission (after 72 h) was more frequent. Severity of patient state was estimated on SAPS and SOFA multifactorial scoring scales. Disease development was controlled by ultrasound scanning, multispiral computer tomography, X-ray fistulography. All patients underwent duodenoscopy, videolaparoscopy with drainage of abdominal cavity for subsequent peritoneal lavage. In the main group endoscopic papillosphincterotomy was used for decompression and lithoextraction.Results. In the main group the direct correlation between disease duration and frequency of acute pancreatitis development was revealed. Course of pancreatic necrosis were determined by volume of pancreatic lesion. Thus correlation between extent of necrosis and increase of SAPS and SOFA scale scores is confirmed, that indicates level of intoxication and multiorgan failure. Subtotal and total PN in main group (63,6%) was more frequent, than in control (37,2%). Local complications, including infected PN, in both study groups developed with identical frequency. On a background of major duodenal papilla stone in a pattern of purulent complications lesser sac abscesses (р=0,010) and peripancreatic necrosis — 8 of 33 (24,2%) were more commonly registered in comparison to alimentary pancreatic necrosis — 1 of 43 (2,3%). The general mortality was 25% (19 of 76 patients), the number of lethal outcomes in the main group was 2 times higher (36,4%), than in control (16,3%).Conclusion. Pancreatic necrosis on background of major duodenal papilla stone is characterized by severe course with development of multiorgan failure and high mortality. Form of PN does not affect infection rate. In treatment of biliary pancreatic necrosis duly decompression of major duodenal papilla is required.